2013
DOI: 10.1073/pnas.1314427110
|View full text |Cite
|
Sign up to set email alerts
|

Superpriming of synaptic vesicles after their recruitment to the readily releasable pool

Abstract: Recruitment of release-competent vesicles during sustained synaptic activity is one of the major factors governing short-term plasticity. During bursts of synaptic activity, vesicles are recruited to a fast-releasing pool from a reluctant vesicle pool through an actin-dependent mechanism. We now show that newly recruited vesicles in the fast-releasing pool do not respond at full speed to a strong Ca 2+ stimulus, but require approximately 4 s to mature to a "superprimed" state. Superpriming was found to be alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
111
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(118 citation statements)
references
References 27 publications
7
111
0
Order By: Relevance
“…Interestingly, dynamin KO leads to alteration of actin polymerization and reorganization in other types of cells (34,66). A role for actin in vesicle recruitment has also been reported (73,83,84). Similarly, Lat-B caused an apparent enhancement in short-term depression in our study.…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, dynamin KO leads to alteration of actin polymerization and reorganization in other types of cells (34,66). A role for actin in vesicle recruitment has also been reported (73,83,84). Similarly, Lat-B caused an apparent enhancement in short-term depression in our study.…”
Section: Discussionsupporting
confidence: 86%
“…Slow superpriming induced by activation of the PLC-DAG pathway has been observed before in the calyx of Held under voltage clamp, using step depolarizations (33). In hippocampal synapses, superpriming was shown to depend on the presence of at least one isoform of rab3 (32).…”
supporting
confidence: 58%
“…At the calyx of Held, potentiation of neurotransmitter release by 1-oleoyl-2-acetyl-sn-glycerol (OAG), a more physiological substitute for PdBu, has been interpreted as a slow maturation process of SVs, following their recruitment to the readily releasable pool (33). This process was found to display distinct pharmacology, involving PLC and DAG, and to take several seconds for completion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S2). Monte Carlo simulations of these results indicated that, at 4 wk, the release probability of docked SVs is reduced for the first and second stimulation, possibly reflecting a decrease of the percentage of high release probability "superprimed" SVs (39,40). In addition, simulations indicated a reduction of the initial occupancy of the replacement site at 4 wk (Fig.…”
mentioning
confidence: 87%